Biodiesel Production from Waste Cooking Oil using Induction Heating Technology - RA Nurul Moulita; Rusdianasari Rusdianasari; Leila Kalsum (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2020)
Kerupuk and kemplang industries produce at least 65 liters of waste cooking oil per production. One form of the application of science and technology in the field of new and renewable energy can be done in processing the waste oil from industrial production through the conversion process into one of the environmental friendly alternative fuels, biodiesel. Biodiesel production process can be carried out by various methods, such as utilizing induction heating technology. This technology has non-contact properties that do not interfere with the reactions that occur because of its application, which produces heat from the workpiece. This study uses waste cooking oil as raw material with variations in the molar ratios 1:3, 1:4, 1:5, 1:6, and 1:7. The analysis showed that the maximum biodiesel production was used of 1: 7 molar ratio with 86.95% yield, 0.86 gr/cm3 of density, 5.73 cSt of viscosity, 190oC of flash point, and 0.44 mg-KOH/gr of acid number. The using this ratio produces maximum yield and following SNI.